ENGLISH-MAJORED STUDENTS’ MOTIVATION IN ENGLISH LANGUAGE LEARNING AND THEIR USE OF READING STRATEGIES: RESEARCH PERSPECTIVES - Thao, Tran Quoc; Long, Nguyen Hoang Chau (VNU Journal of Foreign Studies; Vol 37 No 1, 2021)
Reading plays a vital role in improving second/foreign language learning as it can encourage the development of autonomous learners. Furthermore, ESL/EFL learners’ use of reading strategies can be affected by their learning motivation, which can result in the high or low frequent use of reading strategies in reading comprehension. The present study, therefore, investigated the motivation in English language learning and the use of reading strategies among English-majored freshmen at a university in Bac Lieu province, Vietnam. A questionnaire was used to collect data from 180 English-majored freshmen, six of whom took part in semi-structured interviews. The results showed that participants had a high level of motivation in English language learning, and their metacognitive strategies worked better with their reading comprehension than their cognitive and social/affective strategies. The study further unraveled that the more participants were motivated in English language learning, the more they employed metacognitive and cognitive strategies in reading comprehension.